Clínica saúde e educação: estratégias de cuidado com usuários de drogas - Oliveira, Leonardo Kozoroski (2017)
This study has as a proposal to present some crossings from educational clinical issues within th cara with the users of alcohol and other drugs. Through a clinical perspective, patients, professionals, families, stagg and whoever the agents involved are, the can inaugurate clinic educational strategies. Through a clinical trial analysis of field constructed diaries from caring strategies with users, cartography assumes na experimentation time and clinical invention. Cartography made possible to think the clinic as educational attitude, without leaving aside its relationship with health. The multiplicity of life boosted by care strategies enhanced a willingness learning (STIRNER, 2001) where therapist-apprentice-patient-professor had coexisted. Here Everyone involved have established multiple roles, without depending exclusively on a formal recognition. The opening of space for invention for which the one who is attending tbe Psychosocial Attention Center (CAPS-AD) could experience new possibilities of care, voiced the dormant caregiver inside the patient once mere drug user – here it is noticed the education as a horizon of possibilities.